The Garland handbook of African music - Stone, Ruth M. (Routledge, 2008)
The Garland Handbook of African Music is comprised of essays from The Garland Encyclopedia of World Music: Volume 1, Africa (1997). Revised and updated, the essays offer detailed, regional studies of the different musical cultures of Africa and examine the ways in which music helps to define the identity of this particular area.